2009
DOI: 10.1111/j.1365-2664.2009.01627.x
|View full text |Cite
|
Sign up to set email alerts
|

Valuing nature‐conservation interests on agricultural floodplains

Abstract: Summary 1.The ecosystem approach and evaluation of ecosystem services is gaining increasing attention from scientists, practitioners and policy makers. An important part of this process is to establish the 'value' of the nature-conservation assets within an area. This value can then be compared with data for other ecosystem services to identify management priorities under different future scenarios. However, there is little consensus on how to perform such an evaluation. In this study, we assess seven methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Spearman's rho nonparametric correlations were used to quantify these relative rankings, both for intersite comparisons, and to compare ranks of services between the monetary values and the normalized nonmonetary values for each site. This methodology follows the practice of previous studies in which mean scores have been compared directly (e.g., Rouquette et al 2009). However, this alone does not account for the variation surrounding these means.…”
Section: Comparisons Between Sitesmentioning
confidence: 99%
“…Spearman's rho nonparametric correlations were used to quantify these relative rankings, both for intersite comparisons, and to compare ranks of services between the monetary values and the normalized nonmonetary values for each site. This methodology follows the practice of previous studies in which mean scores have been compared directly (e.g., Rouquette et al 2009). However, this alone does not account for the variation surrounding these means.…”
Section: Comparisons Between Sitesmentioning
confidence: 99%
“…In addition, Watts et al [38] found that increasing organic carbon in soil by 0.1% could reduce the specific plough draught by 5 kPa, which represents a fuel saving of more than 5%. Arable land that helped control flooding could make a large and valuable contribution to both the full economy of the UK [39] and to environmental quality downstream. Clearly not all land can perform all services simultaneously, but UK arable production managed as a whole might, even if not all in the same place.…”
Section: Increase Es and Functionality Of Farmed Land (F)mentioning
confidence: 99%
“…The distinction between 'upland' and 'lowland' BAP habitats, for example, heathland in Pumlumon and Ennerdale, was determined by calculating the area above or below 300 m using a digital terrain model (Maddock 2008). Second, an Ecological Impact Assessment (EcIA) was conducted following Rouquette et al (2009). This involved scoring habitats present within each study area on a scale of 1-6, reflecting their conservation importance (ranging from being a local to an international priority) and significance (ranging from <1% regional resource of the habitat to >5% national resource, within a case study area).…”
Section: Biodiversity Valuementioning
confidence: 99%
“…This involved scoring habitats present within each study area on a scale of 1-6, reflecting their conservation importance (ranging from being a local to an international priority) and significance (ranging from <1% regional resource of the habitat to >5% national resource, within a case study area). The mean score for all habitats across each site was then calculated, following Rouquette et al (2009).…”
Section: Biodiversity Valuementioning
confidence: 99%